First FRCA anatomy : practice cases - Exley, Claire; Minks, David; Tingerides, Constantinos; Uttley, Ashley (JP Medical, 2013)
First FRCR Anatomy: Practice Cases offers up-to-date and comprehensive coverage of practice cases for trainees preparing for the First FRCR Anatomy exam. Chapters are mapped to the syllabus to deliver structured revision in all the key topics, allowing trainees to focus on areas of weakness. Featuring a wealth of practice cases and two mock papers, this book is an essential revision tool to maximise chances of exam success. It includes over 230 high-quality images, reflecting the breadth of topics encountered in the actual exam. It gives practical advice on how to approach revision and useful.